Research Trend of Socio Scientific Issues on Chemical Kinetic Materials: Literature Review - Radjawaly Usman Rery; Tri Padila Rahmasari (STAI Hubbulwathan Duri, 2023)
An individual's success in the 21st century can be measured by their ability to utilise knowledge to enhance their personal qualities. This development can be initiated by enhancing fundamental scientific knowledge. The objective of this study is to examine the correlation between research advancements and socioscientific difficulties in the field of chemistry, with the purpose of aiding advanced researchers in identifying new cutting-edge research topics. This literature evaluation includes 20 selected articles based on specific inclusion criteria: 1) past five years (2018-2020). 2) accredited by SINTA and indexed at Scopus. 3) Research opportunities in Indonesia 4) Keyword: Journal on socio-scientific issues and reaction rates. Academic journals can be discovered by utilising the search engine